The Impact of US Pressure on Saudi Arabia to Achieve Political and Security Reforms (2009-2016) - Alhilaly , Ali (Dirasat: Human and Social Sciences, 2022)
The purpose of the current study is to examine Saudi political reforms from 2009-2016. These reforms came as a result of continued US pressure post-September events in order to change its conservative policy in many files such as Institutional reform, the violation of human rights, and effectively participating in combating terrorism and extremism, where it was accused of supporting terrorism post-September events. The Saudi political system did not put the issues of political reform on the list of its priorities pre-September events, and the details of these issues were not subject to US pressure compared to the rest of the other files such as oil, and military, commercial and economic cooperation. The importance of the study stems from the fact that it is going to be one of these few studies that have focused on the file of political reforms in Saudi Arabia in detail. That could be considered as an addition to the existing literature on this subject. The study has used a systems analysis approach. It is one of the most widely intellectual frameworks in studying the internal or external political activity of any country. The study concludes that the US pressure under the Obama administration led to accelerating political reforms and human rights in Saudi Arabia